2016
DOI: 10.2174/0929867323666160229114111
|View full text |Cite
|
Sign up to set email alerts
|

Niemann-Pick C1-Like 1 (NPC1L1) Inhibition and Cardiovascular Diseases

Abstract: Circulating levels of cholesterol derive from either endogenous production or intestinal absorption of dietary and biliary cholesterol. Niemann-Pick C1-Like 1 (NPC1L1) is a transmembrane protein that plays a key role in the intestinal absorption of cholesterol by facilitating its uptake through vesicular endocytosis. NPC1L1 is the molecular target of ezetimibe which binds its extracellular loop and inhibits sterol absorption without affecting the absorption of other molecules. Ezetimibe significantly reduces p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 102 publications
(142 reference statements)
0
23
0
3
Order By: Relevance
“…Our structures show that the cholesterol molecule could trigger the formation of the structural cluster composed of CLR-6, PS-like molecule, and Loops 3-4 and 7-8, while binding with EZE would disrupt this cluster. Because EZE is a clinical drug used to reduce intestinal cholesterol absorption by targeting NPC1L1 ( 35 ), it is thereby reasonable to postulate that the SSD structural cluster is critical for the cellular cholesterol uptake mediated by the human NPC1L1. To test this hypothesis, we generated NPC1L1 variants, in which some residues involved in the interactions within the cluster were mutated, including L649R, L649R-Y654A, G652A-S653A, and L827F-L828A ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Our structures show that the cholesterol molecule could trigger the formation of the structural cluster composed of CLR-6, PS-like molecule, and Loops 3-4 and 7-8, while binding with EZE would disrupt this cluster. Because EZE is a clinical drug used to reduce intestinal cholesterol absorption by targeting NPC1L1 ( 35 ), it is thereby reasonable to postulate that the SSD structural cluster is critical for the cellular cholesterol uptake mediated by the human NPC1L1. To test this hypothesis, we generated NPC1L1 variants, in which some residues involved in the interactions within the cluster were mutated, including L649R, L649R-Y654A, G652A-S653A, and L827F-L828A ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Afterward, CEs and TG, under the action of MTTP, form chylomicrons, which are then secreted into the lymphatic system [ 72 ]. Studies have reported that inhibition of intestinal cholesterol absorption effectively lowered the plasma LDL-C level [ 73 ] and reduced the risk of CVD [ 74 ]. Thus, it is necessary to block excessive absorption of cholesterol from the diet and bile [ 75 ].…”
Section: Major Cholesterol Regulatory Mechanisms Of Phytochemicalsmentioning
confidence: 99%
“…Ezetimibe reduces intestinal uptake of dietary and biliary cholesterol by inhibiting the interaction with the Niemann-Pick C1-like protein 1 (NPC1L1) [30]. Consequently, the delivery of diet cholesterol to the liver is reduced, thus favouring the increase of hepatic LDLR expression and reducing LDL-C plasma levels.…”
Section: ) Patients With Statin-intolerancementioning
confidence: 99%